Workshop "Natural Pastures and Mobile Animal Husbandry under Pressure: The Cases of Lapland and the Tibetan Plateau", 12-14 June 2002, University of Oulu, Oulu, Finland. - Haugerud (ed. in chief), R.E.; Manderscheid, A.; Colpaert (iss. eds.), A. (Rangifer, 2004)
This special issue contains extended and refereed versions of eight papers presented in the workshop.